ELITE TRANSGENIC LINES OF BASMATI-370 REVEALED HIGH LEVEL OF LODGING RESISTANCE UNDER FIELD CONDITIONS - Mahmood-ur-Rahman (Pure and Applied Biology, 2012)
Lodging decreases crop yield, photosynthesis and grain quality. Three transgenic lines of Basmati-370 containing two Bt genes (cry1Ac & cry2A) were evaluated in the field along with non-transgenic parent as control. The experiment was repeated for consecutive two years. Transgenic rice revealed tremendous morphological variations associated with lodging such as short stature, more number of nodes, less internodal length, etc. The transgenic plants were 33% short in stature while average number of nodes was 3.4 as compared to 4.2 in control. Internodal length in transgenic plants ranged 6.41-8.61cm while in control it was found 14.0cm. These altered characteristics of plants made them resistant to lodging by conferring stiffness to the stem. The elite transgenic lines were 88% more resistant to lodging during the first year while they revealed 78.5% resistance in the second year. The transgenic lines were statistically different from the control during both of the years. Thus, it can be concluded that the elite transgenic lines of Basmati-370 are resistance to lodging as compared to its untransformed counterpart.